2013
DOI: 10.1128/iai.00298-13
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria Prophage Repressor Implicated in Gonococcal Pathogenesis

Abstract: c Neisseria gonorrhoeae, the causative agent of the sexually transmitted disease gonorrhea, can infect and colonize multiple mucosal sites in both men and women. The ability to cope with different environmental conditions requires tight regulation of gene expression. In this study, we identified and characterized a gonococcal transcriptional regulatory protein (Neisseria phage repressor [Npr]) that was previously annotated as a putative gonococcal phage repressor protein. Npr was found to repress transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…A second target, NGO1646, is predicted to encode a phage-associated protein in the N. gonorrhoeae FA1090 genome. While little is known regarding the role of phage-associated proteins in the regulatory pathways of N. gonorrhoeae, previous studies by our group have identified one such phage-associated protein, Npr, which is involved in gonococcal pathogenesis (36). Lack of Npr leads to increased adherence to and invasion of epithelial cells as well as enhanced colonization in a gonococcal mouse model of infection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A second target, NGO1646, is predicted to encode a phage-associated protein in the N. gonorrhoeae FA1090 genome. While little is known regarding the role of phage-associated proteins in the regulatory pathways of N. gonorrhoeae, previous studies by our group have identified one such phage-associated protein, Npr, which is involved in gonococcal pathogenesis (36). Lack of Npr leads to increased adherence to and invasion of epithelial cells as well as enhanced colonization in a gonococcal mouse model of infection.…”
Section: Discussionmentioning
confidence: 98%
“…At 2 h, 5 h, and 24 h postincubation, total cell-associated and intracellular bacteria were measured by counting CFU. Counting of total cell-associated bacteria and intracellular bacteria was carried out as described previously (36). The experiments were repeated four times with F62 strains and three times using N. gonorrhoeae FA1090 opaA-K wild-type, arsR, and arsR-complemented strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon of silent Fur binding has been recently demonstrated with a novel gonococcal phage repressor protein, Npr [48]. Under In vivo conditions, some Fur binding sites may not be accessible due to the binding of other transcriptional regulators and nucleoid-associated proteins including H-NS (histone-like nucleoid structuring protein), IHF (integration host factor), HU (heat unstable protein) and Fis (factor for inversion stimulation) [56].…”
Section: Discussionmentioning
confidence: 98%
“…Although Mu-like phages were not found in N. gonorrhoeae genomic sequences (104), five different double-stranded DNA (dsDNA) lysogenic phages were identified in strain FA1090 (Ngoφ1-5), and their repressor genes were shown to be functional in E. coli (121). A repressor from Ngoφ4 has been suggested to affect N. gonorrhoeae pathogenesis by regulating the ability of gonococci to adhere and invade human cervical cells (38). Although the dsDNA phages were not able to form plaques in commensal Neisseria, lambda-like particles from N. gonorrhoeae culture supernatants, presumed to be from the integrated prophages, were visualized by electron microscopy (121).…”
Section: Bacteriophagesmentioning
confidence: 98%